Bilateral Atypical Femoral Fracture(AFF) After Teriparatide and Subsequent Anti-Resorptive Therapy: A Management Dilemma - Reddy, Chandrika (J Endocr Soc, 2021)
Introduction: Femoral fractures carry devastating morbidity for long term ambulation. Atypical femoral fractures (AFF) are uncommon, and bilateral AFFs are more rare with added post-fracture limitations. We report two patients with bilateral AFFs despite receiving teriparatide (TPTD). Case 1: A 72 y.o. Filipino lady with osteoporosis since late 1990 was treated with bisphosphonates (BP) intermittently over 25 years with drug holidays for dental work. She stopped alendronate in mid-2013 and continued raloxifene. She suffered a spontaneous left mid-femur AFF in June, 2015 that was treated with intramedullary (IM) rod and nailing. In July, 2015 she started TPTD 20 mcg daily for 23 months until May, 2017. Alendronate was restarted weekly. In December, 2018 she developed right thigh and hip prodromal pain without x-ray changes. In April, 2019 (46 months after the left AFF and 23 months after TPTD), she sustained a spontaneous right sub-trochanteric AFF. BP was stopped. After IM rod and nailing, she began a second course of TPTD. Case 2: 72 y.o Caucasian lady with osteoporosis since 2000 was treated with alendronate until April, 2006. She was switched to daily TPTD for 22 months from May, 2006 to March, 2008. Oral BP was resumed in April, 2008. She suffered a left AFF in November, 2009; BP was stopped in March, 2010. In July, 2010 she sustained a right AFF (9 months after the left AFF and 28 months post-TPTD). Each spontaneous AFF occurred after prodromal pain, and each was treated with IM rod placement with nailing. She received BP infusion in 2011 and TPTD from March, 2012 to March, 2014. DXA scan in 2020 showed lumbar spine osteopenia. She currently takes calcium and Vit D supplementation. Discussion: TPTD is reported as a potential treatment for enhancing AFF healing, bone mineral density and pain resolution. The expectation is that it might prevent contralateral AFF. No randomized studies of prevention of AFF with TPTD exist. Available reports show variable results. Prolonged presence of BP in bone may contribute to this variation. We identified 7 reported AFF patients treated with TPTD who then developed a contralateral AFF. We found 2 patients with new AFF after TPTD as in our Case 2. In all cases there was previous exposure to BP. Perhaps the 28–30% risk of a contralateral AFF within 4 years in the setting of BP is irremediable. Conclusion: TPTD increases healing of AFF in some reports, but prevention of an initial or further AFF has not been well documented. Our 2 patients and 9 others reported suggest a possible subset with increased sensitivity to the effect of BP and increased AFF risk. The best choice after TPTD is unclear, but it may include permanent removal of anti-resorptive agents. The anti-sclerostin antibody romosozumab also has been associated with AFF. Choices are limited for these patients other than excellent surgical care, adequate calcium/vitamin D intake, and periodic imaging as symptoms dictate.